Abstract To Islamic Insurance (Takaful) - Cheikh, Bouaziz (Assurances et gestion des risques / Insurance and Risk Management, 2013)
Takaful is the means of bringing the social and economic benefits of modern insurance coverage, in a form consistent with their religious beliefs, to Muslims and to the merging economics of many predominantly Muslims countries. As such, the development of Takaful is crucial, both to social inclusion in non–Muslim countries, and to economic development in a number of countries with emerging market economies. It is therefore only surprising that the Takaful industry is undergoing a period of rapid growth. Yet the development of Takaful faces some formidable barriers that are largely due to the complex structure of takaful understandings and the unresolved issues associated with it. These issues contribute to making the development of an appropriate legal and regulatory infrastructure, as well as financial reporting, corporate governance, rating and other related matters, problematic for the Takaful industry.